PENGEMBANGAN MEDIA POP UP BOOK PADA PEMBELAJARAN TEMATIK TEMA 8 LINGKUNGAN SAHABAT KITA KELAS V SD - Winda Sari; Muhammad Noer Fadlan (Jurnal Cakrawala Ilmiah, 2024)
This research aims to develop pop up book media that is suitable for use in thematic learning of Theme 8 Our Friend's Environment for Class V Elementary School. This research is development research (Research and Development) using the ADDIE development procedure which consists of 5 stages. The test subjects in this research were media experts, material experts, teacher responses and student responses. The object in this research is the Pop Up Book Media in Thematic Learning Theme 8 Our Friendly Environment which is suitable for use in the thematic learning process in class V. The instrument used to collect data is a validation questionnaire given to several expert validators, namely media expert validators, material expert validator and learning expert validator. The total score obtained from media expert validation was 89.4, from material expert validation, namely 87.5, from learning experts 86.5 and from student responses a score of 91.4 was obtained. The average score from the experts' assessments is 88.47. From these scores it can be said that the Pop Up Book media Theme 8 "Our Friend's Environment" which was developed is "Very Suitable" for use in the thematic learning process in class V UPTD SDN 010143 Perkebunan Aek Tarum.